Ice conditions interannual variability in the Antarctic Peninsula region and its connection with the atmospheric circulation indexes - Ju. V. Artamonov; E. A. Skripaleva; A. O. Bukatov (Ukrainian Antarctic Journal, 2008)
The features of the interannual variability of the sea ice of the different closeness are investigated from 1969 to 2002 on the base of data BADS HadISST ICE. The cross-correlation connections between variability of the ice closeness, the air temperature at the Antarctic stations and the indexes of atmospheric circulation SOI (Southern oscillation) and AAO (Antarctic oscillation) are estimated. It is shown that maximal interannual variations are characteristic for the ices of the 90 – 100% closeness. It is noted than the maximal anomalies of the ice closeness in ENSO periods are observed in the Antarctic Peninsula region and Sodruzhestvo and Ross seas. The reaction on the El Niño events is most shown in the behavior of positive anomalies of the ice closeness. The high cross-correlation connections on the 95% level of statistical significance between SOI, AAO and ice closeness to the west of the Antarctic Peninsula are founded. The inverse correlation between AAO and ice on the lag to one year to be observed, between SOI and ice – the direct correlation on the lag about 6 year. High inverse correlation with the zero lags is discovered between the air temperature and the ice closeness near the Antarctic stations.